Timing as Signal: Submission Hour as a Predictor of Academic Performance in an Engineering Design Module - Pierre Eduard Hertzog (Faculty of Teacher Training and Education Universitas Sebelas Maret Surakarta, 2026)
Learning management systems record the exact time students submit their work, yet this behavioral trace is rarely used to examine student performance. This study investigated whether the hour at which a student submits the most technically demanding formative assessment in an engineering design module predicts both that assignment mark and the final module outcome. Data were drawn from three consecutive cohorts (2023–2025) of students enrolled in Design Project III, a Level 6 module at the Central University of Technology, Free State, South Africa. Submission timestamps for 387 student-year records were extracted from the Blackboard Learning Management System and classified into four deadline-day time bands. Statistical analysis revealed a significant negative relationship between submission hour and Submission 2 mark (Pearson r = −0.21, p < .001), with students who submitted in the last hour (16:00–17:00) scoring a mean of 54.32% compared with 64.22% for morning submitters (a gap of 9.9 percentage points). This effect carried through to the final module mark (r =−0.15, p = .003). Critically, no comparable effect was found at the summative final submission (p =.619), confirming that the relationship is specific to the intermediate, high-complexity assessment stage. These findings suggest that submission timing may serve as a practical early warning indicator of academic risk in engineering design modules.